Educational Objectives The skill of writing Arabic to other speakers at the level of A1 and A2 in perspective of the common European framework for teaching languages - Talqis Nurdianto; Zainal Abidin Hajib; Noor Azizi bin Ismail (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
Educational Objectives in the Skill of Writing Arabic to Other Speakers at The Level of A1 And A2 in Perspective of The Common European Framework for Teaching LanguagesTalqis Nurdianto, Zainal Abidin Hajib, Noor Azizi bin IsmailUniversity of Muhammadiyah Yogyakarta, Universiti Sains Islam Malaysia, Universiti Sains Islam Malaysiatalqis@umy.ac.id, drzainal@usim.edu.my, azizi12@usim.edu.myAbstractArabic is a second language for the non-native, there were several methods for learning and teaching Arabic which different from the learning and teaching methods of first language. The difficulty of understanding Arabic listening, speaking, reading, and writing is not due to the language itself. Complete it, because every language in the world is difficult in its various capacities and may return to the method used. The way letters are written in Arabic is different in Latin with written spelling rules. The writing skill is one of the language production skills, and the production skill has the most difficulty of reception skills. This research aims to reveal and translate educational standards of writing skill in Arabic for non-native speakers in light of the common European reference framework for language education focused on the two levels (A1 and A2). The researcher dives deep into the sea of the European reference framework to extract a festival of writing skill levels for beginners by descriptive analytical method. The researcher collected information on the common European reference framework for language education and analyzes the general standards in Arabic language teaching by translating levels of writing skill. Several results were presented to us with a model of educational goals table, writing skill, that facilitates curriculum development in educational institutions. The curriculum that defines the method, means, and tests used in educational activitiesKeywords: Skill, Writing, level, framework, Europeأهداف تعليمية مهارة الكتابة العربية للناطقين بغيرها على مستوي (A1  و A2) في ضوء الإطار المرجعي الأوروبي المشترك لتعليم اللغاتتلقيس نورديانتو، زين العابدين حاجب، نور عزيزي بن إسماعيلجامعة محمدية يوكياكرتا، جامعة العلوم الإسلامية الماليزية, جامعة العلوم الإسلامية الماليزيةtalqis@umy.ac.id, drzainal@usim.edu.my, azizi12@usim.edu.my الملخصاللغة العربية لغة أجنبية للناطقين بغيرها، وطريقة تعليم وتعلمها تختلف تماما بلغة الأم. صعوبة فهم العربية استماعا، ونطقيا، وقراءة، وكتابة لا ترجع إلى اللغة بذات أكملها لأن كل لغة في العالم صعوبة باختلاف قدرها وقد تعود إلى المنهج المستخدم. إن طريقة كتابة أحرف اللغة العربية تختلف باللاتينية تتعلق بقواعد الإملاء كتابية. مهارة الكتابة من احدى مهارتي الإنتاج اللغوي، ومهارة الإنتاج ذو أكبر صعوبة من مهارات الاستقبال. ويهدف هذا البحث لكشف وترجمة معايير تعليمية مهارة الكتابة اللغة العربية لغير الناطقين بها في ضوء الإطار المرجعي الأوروبي المشترك لتعليم اللغات الذي يتركز على المستويين (A1 وA2). ويغوص الباحث في عمق بحر الإطار المرجعي الأوربي ليستخرج مهرجان مستويي مهارة الكتابة للمبتدئين بالطريقة الوصفي التحليلي. جمع الباحث معلومات عن الإطار المرجعي الأوروبي المشترك لتعليم اللغات ويحلل المواصفات العامة في تعليم اللغة العربية بترجمة مستويات لمهارة الكتابة. وتطلع علينا عدة نتائج بنموذج جدول أهداف تعليمية مهارة الكتابة الذي يسهل واضع المنهج في المؤسسات التعليمية. والمنهج الذي يحدد الطريقة والوسيلة والاختبارات المستعملة في الأنشطة التعليمية.الكلمات المفتاحية: مهارة، كتابة، المستوى، الإطار، الأوروبي.